2022
DOI: 10.26603/001c.32545
|View full text |Cite
|
Sign up to set email alerts
|

Nonoperative Management of Traumatic Acromioclavicular Joint Injury: A Clinical Commentary with Clinical Practice Considerations

Abstract: Traumatic injuries of the acromioclavicular joint result in pain and potentially long-term alterations in scapulohumeral rhythm that occurs due to disruption of the clavicular strut function which is integral to scapular kinematics. Nonoperative treatment remains a valid option in most acromioclavicular joint injuries with the potential of minimizing pain and restoring scapulohumeral rhythm. However, few studies have provided nonoperative treatment details. Therefore, the purpose of this clinical commentary is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 100 publications
0
12
0
Order By: Relevance
“…Periscapular strengthening may be helpful, but optimal muscle function demands joint stability and clavicular strut function in order to be effective. 15,18…”
Section: Pathomechanics and The Question Of The Type III Injurymentioning
confidence: 99%
See 4 more Smart Citations
“…Periscapular strengthening may be helpful, but optimal muscle function demands joint stability and clavicular strut function in order to be effective. 15,18…”
Section: Pathomechanics and The Question Of The Type III Injurymentioning
confidence: 99%
“…A recent systematic review of the literature disseminated information specific to non-operative AC joint treatment, noting that the literature has not been helpful in guiding clinicians on how to best manage AC joint injury conservatively. 18 The review identified numerous concerns including low quality critical appraisal evidence as well as methodological inconsistencies within (robust detail for operative measures and limited to non-existent detail for non-operative measures) and between studies (injury heterogeneity, surgical technique variations, and variations in outcome measures). The authors recommended an approach to treatment focused on restoring dynamic function rather than cosmetic realignment.…”
Section: Treatment Guidelinesmentioning
confidence: 99%
See 3 more Smart Citations